Analisis Pengembangan Usaha Budidaya Ikan Patin Dan Produk Olahannya Terhadap Pendapatan Pembudidaya Dan Ekonomi Masyarakat Sekitar Menurut Perspektif Ekonomi Islam ( Studi Kasus Kelompok Budidaya Desa Teluk Ketapang, Pemayung, Batang Hari ) - Azizatul Mahfudhoh; Amri Amir; Aditya Pratama (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to identify problems and efforts in developing fish farming business and its processed products in Teluk Ketapang Village, as well as its impact on farmers and surrounding communities according to the perspective of Islamic economics. This type of research is descriptive qualitative research, data collected and obtained through interviews, observation, and documentation. Testing the validity of data using triangulation and member check techniques. The results of this study show that problems in developing catfish farming business in Teluk Ketapang Village include lack of knowledge about aquaculture and limited funds as capital, while there are other problems in the form of internal problems of the Bina Sejati group and problems about marketing occur in the Harapan Maju group. Development efforts are carried out through training, funding applications, and market expansion, reflecting the principles of Islamic economics that emphasize diversity, common prosperity, and sustainability. The positive impact of this cultivation business can be seen in increasing the income of cultivators and the economy of the surrounding community, as well as social contributions such as the opening of job opportunities and the practice of giving sadaqah, making this business in accordance with Islamic economic values that emphasize social responsibility and environmental conservation.